Analisis Masalah dan Solusi Kompetensi Lulusan PKn SD - Muhammad Kaulan Karima; Muhammad Mona Adha; Ridwan Syukri; Ana Putri Sholihah; Dhea Ovita; Sattya Dewi Larasati; Meino Rinaldi; Abdul Haris; Sulistiana Sulistiana; Pricilia Deyalita Utami (Departement of Mathematics Education, 2025)
Civic Education (PKn) plays a crucial role in shaping the character and civic competencies of students, particularly at the elementary school level. One of the main instruments for achieving national education goals is the Graduate Competency Standards (SKL), which set the minimum competencies that students must acquire upon completing their education. This study aims to analyze the challenges and solutions related to the implementation of SKL in the Civic Education subject in elementary schools. Using a descriptive qualitative approach with a literature review method, the study identifies several key issues: disparities in educational access, unequal implementation of SKL, and the impact of economic factors on the achievement of graduate competencies. Proposed solutions include improving teacher training and quality, utilizing technology in learning, adapting curricula to local conditions, conducting outreach and fostering collaboration with the community, and enhancing educational infrastructure. The implementation of these solutions is expected to reduce disparities in the application of SKL in Civic Education and strengthen the character formation of students in alignment with the values of Pancasila and the 1945 Constitution of Indonesia. This, in turn, aims to cultivate citizens who are active, responsible, and contributive in social and national life.